Natural Variation in Adventitious Rooting in the Alpine Perennial Arabis alpina - Mishra, Priyanka; Roggen, Adrian; Ljung, Karin; Albani, Maria C. (MDPI, 2020)
Arctic alpine species follow a mixed clonal-sexual reproductive strategy based on the environmental conditions at flowering. Here, we explored the natural variation for adventitious root formation among genotypes of the alpine perennial Arabis alpina that show differences in flowering habit. We scored the presence of adventitious roots on the hypocotyl, main stem and axillary branches on plants growing in a long-day greenhouse. We also assessed natural variation for adventitious rooting in response to foliar auxin spray. In both experimental approaches, we did not detect a correlation between adventitious rooting and flowering habit. In the greenhouse, and without the application of synthetic auxin, the accession Wca showed higher propensity to produce adventitious roots on the main stem compared to the other accessions. The transcript accumulation of the A. alpina homologue of the auxin inducible GH3.3 gene (AaGH3.3) on stems correlated with the adventitious rooting phenotype of Wca. Synthetic auxin, 1-Naphthaleneacetic acid (1-NAA), enhanced the number of plants with adventitious roots on the main stem and axillary branches. A. alpina plants showed an age-, dosage- and genotype-dependent response to 1-NAA. Among the genotypes tested, the accession Dor was insensitive to auxin and Wca responded to auxin on axillary branches.